2020
DOI: 10.3390/su122410306
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation Characteristics and Response to the Soil Properties of Three Medicinal Plant Communities in Altay Prefecture, China

Abstract: Plant communities and their environments are a vital part of synecology research. In this study, we investigated the characteristics of three typical medicinal perennial herbs, Glycyrrhiza uralensis, Rheum altaicum, and Ferula sinkiangensis, and examined their response to local soil properties in Altay Prefecture, China. A total of 29 species belonging to 15 families and 25 genera were recorded. In terms of the target medicinal plants, the importance value was low and community structures were exceedingly simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Additionally, all four of the D. spathacea populations possessed a large number of young individuals and 3-4 species of other dominant trees in the community, implying that competition for light, water, and nutrients might exist within and among the various species. Indeed, our previous study on the ecological patterns of three kinds of terrestrial medicinal plants in Altay Prefecture, China, also found that competition was one of the most important factors that crucially determined the ecological niche of a species [35]. In this work, the higher D. spathacea population mortality rate in the early age class may be a result of the enhanced intraspecific and interspecific competition.…”
Section: Analysis Of D Spathacea Population Structurementioning
confidence: 49%
See 1 more Smart Citation
“…Additionally, all four of the D. spathacea populations possessed a large number of young individuals and 3-4 species of other dominant trees in the community, implying that competition for light, water, and nutrients might exist within and among the various species. Indeed, our previous study on the ecological patterns of three kinds of terrestrial medicinal plants in Altay Prefecture, China, also found that competition was one of the most important factors that crucially determined the ecological niche of a species [35]. In this work, the higher D. spathacea population mortality rate in the early age class may be a result of the enhanced intraspecific and interspecific competition.…”
Section: Analysis Of D Spathacea Population Structurementioning
confidence: 49%
“…Among the investigated 284 D. spathacea trees on Hainan Island, their age classes were as follows: There were 58, 188, and 38 young, middle, and old individuals, accounting for 20.42%, 66.20%, and 13.38% of the population, respectively (Figure 2). Specifically, the numbers of young individuals in the D. spathacea populations of Bamen Gulf (Wenchang), Qiexin Estuary (Wanning), Qingmei Harbor (Sanya), and Tielu Harbor (Sanya) only accounted for 29.61% (45), 0% (0), 8.16% (4), and 24.32% (9), while the numbers of middle individuals accounted for up to 56.58% (86), 76.90% (35), 83.67% (41), and 70.27% (26) in the four above-mentioned populations (Figure 2). The numbers of old individuals in these D. spathacea populations were the fewest, occupying only a proportion of 13.82% (21), 23.91% (11), 8.16% (4), and 5.41% (2), respectively (Figure 2).…”
Section: Age Class Structure Analysis Of D Spathacea Populationmentioning
confidence: 99%
“…Rhubarb has wide practical applications as fodder and medicinal plants. [2][3][4][5][6]. Rheum compactum and R. wittrokii are included in the Red Book of Kazakhstan (2014) [7] and have the status: Category III -rare species, with declining numbers R. altaicum is a relict and endemic of Eastern Kazakhstan [8].…”
Section: Introductionmentioning
confidence: 99%
“…The complex topography of this region leads to pronounced spatial variations in climate. Precipitation in the lower altitudes ranges from 200 to 300 mm, while the high-altitude mountainous areas receive over 600 mm of rainfall [6]. Precipitation increases with elevation, while temperatures decrease, resulting in significant vertical gradient changes.…”
Section: Introductionmentioning
confidence: 99%